Mercury and methylmercury levels in soils associated with coal-fired power plants in central-northern Chile. (December 2019) - Pérez, Pablo A.; Hintelmann, Holger; Lobos, Gabriela; Bravo, Manuel A.
Abstract: Mercury pollution is a worldwide problem, and is associated with a number of natural and anthropogenic processes. The present work, conducted in Chile, a country that has traditionally depended heavily on fossil fuels for power generation, examines total mercury (THg) and monomethylmercury (MMHg) concentrations in soils across different sites exposed to coal fired power plant emissions. Samples from four selected (Renca, Laguna Verde, Las Ventanas, Huasco) and 1 control (Quintay) sites were analyzed using cold vapour and fluorescence spectroscopy (CV-AFS) for THg determination and chromatographic separation with atomic fluorescence detection (DI-GC-AFS) was followed for speciation analysis. From the sites analyzed, Renca and Las Ventanas showed high concentrations of total mercury, exhibiting ranges between 135 – 568 and 94–464 ng g −1 respectively, while Laguna Verde and Huasco exhibited lower values ranged 5–27 and 9–44 ng g −1 respectively. Conversely, analysis of MMHg concentrations showed that only Renca site possessed high values, ranging between 0.1 and 3.0 ng g −1, resulting in this site being considered contaminated. Conversely, other sites showed minimal values comparable to the control site (0.024 ± 0.003 ng g −1 ) in terms of MMHg concentrations. An analysis of the differences between MMHg and THg concentrations in contaminated sites, suggests an overall absence of methylation in soils of Las Ventanas, probably related to the very high levels of soil heavy metals, especially copper. Moreover, the influence of the composition and physicochemical properties of the different soils on the mobility of the species was assessed. Results obtained (as Log Kd) were 3.5 and 4.1 for Renca and Las Ventanas respectively, suggesting low mobility of mercury species in the environment for both sites. Finally, the data obtained allowed us to establish a first approximation of the differences in concentration and mobility of total and MMHg associated with coal fired power plants emission in central-northern Chile, an area previously understudied in a country heavily dependent on fossil-fuels. Highlights: The concentrations of THg and MMHg were measured in soils from sites impacted for coal-fired power plants. The MMHg/THg ratio suggests that some metals, such as copper, could be affecting methylation process. Coal-fired power plants emissions increase the mercury enrichment in soils over most areas studied. Low mobility in mercury species was found in soils for contaminated sites.